Host-parasite associations of the Cratogeomys fumosus species group and their chewing lice, Geomydoecus - Popinga, Alex; Demastes, James W; Spradling, Theresa A; Hafner, David J; Hafner, Mark S (THERYA, 2019)
Chewing lice (Phthiraptera: Trichodectidae) and the pocket gophers (Rodentia: Geomyidae) that they inhabit have shared an intimate historical association that has made them a textbook study for cophylogeny. Herein, we examine the chewing lice found on pocket gophers of the Cratogeomys fumosus species group using DNA sequence data from the mitochondrial cytochrome c oxidase subunit I gene to determine relationships among lice for comparison to published host phylogeny. Although matrix approaches indicate a correlation between host and parasite genetic distances, cophylogenetic reconstruction methods fail to detect a pattern of widespread cophylogeny. In conclusion, this study provides an exception to the rule of host-parasite cophylogeny that could be the result of the young age of the relationships considered herein and the complex history of the Trans-Mexican Volcanic Belt.